Inovasi Pelapisan Glasir Pada Gerabah Di Industri Kecil Dan Menengah : Desa Melikan Kecamatan Wedi, Kabupaten Klaten, Jawa Tengah - Titik Purwanti; Agung N. Jati; Oki Kuntaryanto; Syarifah Aini; Zuyina Luklukaningsih; Anna F. Setianingtyas; Anis Marjukah; Abdul Haris; Kun Ismawati; Endang Wulandari; Nawang Kalbuana (Pengmasku, 2023)
Melikan Village, Wedi District, Klaten Regency is an area that is 90% working as traditional pottery craftsmen with one of the rare ceramic-making techniques in the world, namely the tilt rotation technique. This technique turned out to be a feature that distinguished it from the art of printing pottery and ceramics from other regions with a plain brown, blackish color being its hallmark. The products of this craft have been exported to Switzerland and other countries. The purpose of this community service activity includes improving creative skills and innovating in making pottery and glaze crafts. The method applied in this community service activity is through lectures (counseling), mentoring, and the practice of making pottery with glaze. The existence of this community service activity is able to encourage craftsmen to produce pottery that has been coated with glaze so that it can improve the quality of pottery/ceramics so that it is more marketable in the modern market as it is today.